New developments in composites, copolymer technologies and processing techniques for flexible fluoropolymer piezoelectric generators for efficient energy harvesting. Issue 4 (1st February 2019) - Shepelin, Nick A.; Glushenkov, Alexey M.; Lussini, Vanessa C.; Fox, Phillip J.; Dicinoski, Greg W.; Shapter, Joseph G.; Ellis, Amanda V.
Abstract : A comprehensive review of current developments in flexible fluoropolymer-based piezoelectric generators for sustainable energy harvesting. Abstract : Flexible piezoelectric generators (PEGs) have recently attracted significant interest, as they are able to harvest mechanical energy and convert it to electricity, decreasing reliance on conventional energy sources. These devices enable innovative applications including smart clothing, wearable electronics, on-skin and implantable sensors, as well as harvesting energy from the movement of vehicles, water and wind. Poly(vinylidene fluoride) and related fluoropolymers are the most common flexible piezoelectric materials, widely utilized for their high electromechanical conversion efficiencies, optimal mechanical flexibility, processability and biocompatibility. This critical review covers the processing of fluoropolymers towards the maximization of piezoelectric conversion parameters. Particular emphasis is placed on the correlation between synthetic routes, inclusion of further co-monomers, addition of additives and nanomaterials, as well as processing techniques and the optimized electricity generation in the resultant PEGs, providing an important analysis to complement existing literature. The importance of novel polymer deposition techniques, which reduce reliance on the conventional, highly energetic post-processing steps, is highlighted. Recent advances in fluoropolymer-based flexible PEGs open an array of exciting applications, which rapidly progress towards commercialization. This review provides a timely analysis of this increasingly important field to the cross-disciplinary community of polymer chemists, materials scientists, nanotechnologists, engineers, and industry practitioners.